Islamic Education as a Foundation of Character: a Case Study of the Formation of Noble Morals in Students - Uswatun Khasanah (JIE (Journal of Islamic Education), 2023)
This study aims to determine the important role of Islamic education at the Islamic Institute of Mamba'ul 'Ulum Surakarta in shaping the character of students with noble morals. This study highlights how the integration of Islamic values in the curriculum and daily activities contributes to the development of positive behaviour and harmonious social interactions among students. This study uses a qualitative method with a case study approach. The data analysis technique used is thematic analysis. The results of the study indicate that values such as honesty, responsibility, and empathy, which are instilled through Islamic education, not only strengthen religious beliefs but also shape students into moral and responsible individuals. Character education based on Islamic values has proven effective in fostering a young generation with noble morals. Thus, this study recommends that other educational institutions can adopt a similar approach in character education to create an environment that supports the formation of positive character. This shows the potential of Islamic education as a strong foundation for character education, which can be widely implemented to produce significant social impacts.